Crosslinking agent for improving performance of chitosan film, preparation method and application thereof

CN122878636APending Publication Date: 2026-10-09SHAANXI XIGUO YOUNONG BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868647.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

因此在苹果产区,每个生长季都会产生大量的苹果幼果废弃物,还没有得到很好的处理

Benefits of technology

[0013]1、本发明首次发现,与成熟苹果相比,在苹果疏果过程中作为农业废弃物的苹果幼果中富含苹果果胶,且通常是高甲酯果胶(甲基酯化程度大于50%),其中超过50%的半乳糖醛酸(GalA)羧基被甲酯化,从而降低了纤维表面的负电荷密度。通过碱性脱甲酯可有效地将苹果幼果果渣纤维中的-COO-含量从0.15mmol g-1提高到1.30mmol g-1,通过高压均质转化为具有高纵横比和良好水分散性的苹果幼果纳米纤维(YANF)胶状溶液。这种YANF胶状溶液作为交联剂,其中的-COO-与壳聚糖中的-NH3+发生静电交联,从而显著改善了壳聚糖薄膜的疏水性、机械强度和阻隔性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878636A_ABST
    Figure CN122878636A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of crosslinking agent for improving the performance of chitosan film, preparation method and application.The crosslinking agent is rich in nanofiber with diameter less than 25 nanometers, and the mass fraction of the colloidal liquid is 0.5%-1.5%.The nanofiber is extracted from apple young fruit, and the apple young fruit is removed within 2-3 weeks after pollination and flower drop to the physiological fruit drop period.The present application discloses that the colloidal solution of apple young fruit nanofiber as a crosslinking agent can significantly improve the hydrophobicity, mechanical strength and barrier property of chitosan film, and also maintains excellent biodegradability, completely degrades within 15 days.The chitosan film has excellent freshness preservation and environmental sustainability, providing great potential for the future of sustainable food packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of comprehensive utilization technology of agricultural waste, specifically to a crosslinking agent for improving the performance of chitosan films, its preparation method, and its application. Background Technology

[0002] Plastic packaging is widely used in food packaging due to its cost-effectiveness and superior performance. However, the overuse of plastic packaging has caused serious environmental and food safety problems, mainly because of its poor biodegradability; microplastics and plasticizers can migrate into food and accumulate in the human body. Food preservation films are an important application of petroleum-based plastic packaging and are crucial for the preservation of fruits and vegetables. Utilizing abundant biomass to prepare eco-friendly and sustainable alternatives is essential for reducing the environmental impact of traditional petroleum-based packaging materials.

[0003] Chitosan is a unique cationic polysaccharide composed of D-glucosamine and N-acetyl-D-glucosamine linked by β-1,4-glycosidic bonds. It is the second most abundant polysaccharide globally after cellulose and is widely used in food preservation films. However, limitations of chitosan films, such as strong hydrophilicity, insufficient barrier properties, and unsatisfactory mechanical strength, restrict their widespread application in food preservation. To overcome these shortcomings, existing technologies employ chemical modification, blending with other bio-based polymers such as starch, protein, collagen, cellulose, and pectin, and the addition of crosslinking agents and fillers to improve chitosan films. Among these, bio-based nanofibers, rich in -OH and -COO... - Crosslinking agents, through physical crosslinking (such as electrostatics and hydrogen bonding), significantly improve the aforementioned limitations of chitosan food preservation films. Compared with other methods, bio-based nanofiber crosslinking agents have advantages such as low required amounts, significant improvement in film performance, and simple preparation processes. However, different bio-based nanofiber crosslinking agents have significantly different effects on the performance of chitosan films. For example, lignocellulose nanofibers (LCNF) and bacterial nanocellulose (BNC) are common bio-based nanofibers. BNC is synthesized by microorganisms, resulting in high production costs, while LCNF is extracted from economically viable sources such as wood, fruit and vegetable waste, grain straw, and other cellulose materials through relatively inexpensive physical and chemical processes. Although LCNF has a high aspect ratio and a large specific surface area, its surface -OH groups are non-selective, making it prone to hydrogen bonding crosslinking and self-assembling into bundles and aggregates. This weakens its crosslinking effect with chitosan and limits its dispersibility in chitosan aqueous solutions, making it unsuitable for products such as chitosan films (including composite films or food preservation films). Therefore, finding suitable nanofiber crosslinking agents is crucial for improving the performance of chitosan films.

[0004] Apples are one of the most widely grown and consumed fruits in my country. During apple cultivation, fruit thinning is necessary 2-3 weeks after pollination and flowering, before the physiological fruit drop period. Typically, a cluster of flowers will produce 5-6 small apples; only one needs to be retained, and the others (also known as young apples) should be removed. This ensures the tree can better allocate nutrients, improving fruit quality and yield. Therefore, in apple-producing areas, a large amount of young apple waste is generated each growing season, and this waste has not yet been properly managed. Summary of the Invention

[0005] To address the above problems, this invention proposes a crosslinking agent, preparation method, and application for improving the performance of chitosan films.

[0006] This invention provides a crosslinking agent for improving the performance of chitosan films. The crosslinking agent is a gel-like liquid rich in nanofibers with a diameter of less than 25 nanometers and a mass fraction of 0.5%-1.5%. The nanofibers are extracted from young apple fruits, which are small apples removed within 2-3 weeks after pollination and before the physiological fruit drop period.

[0007] Furthermore, the preparation method of the crosslinking agent is as follows: the dried young apple fruit is crushed and added to a sodium hydroxide solution with a concentration of 0.1-4M at a weight ratio of 1:10-50, and soaked at room temperature for 10-30 hours for alkaline demethylation. Then, the resulting fruit pomace is washed with water until neutral, and then the neutral fruit pomace is continuously treated several times using a high-pressure homogenizer. Water is added during the treatment process to obtain a colloidal liquid rich in nanofibers with a diameter of less than 25 nanometers and a mass fraction of 0.5%-1.5%, which is the crosslinking agent.

[0008] Furthermore, the crushed young apples are added to a sodium hydroxide solution at a ratio of 1:20.

[0009] Furthermore, the sodium hydroxide solution has a concentration of 1M, and the soaking time is 15 hours for alkaline demethylation.

[0010] The present invention also provides the application of the above-mentioned crosslinking agent in the preparation of chitosan film. Chitosan is dissolved in acetic acid solution and stirred until completely dissolved. Then, a plasticizer is added and stirred until completely dissolved. Then, the above-mentioned crosslinking agent is added at a mass percentage of 1%-15% based on the dry weight of chitosan. After mixing evenly, the mixture is allowed to stand until all air bubbles are removed. Then, it is poured into a mold, leveled, and dried at low temperature to obtain the chitosan film.

[0011] Furthermore, the aforementioned crosslinking agent is added at a concentration of 10% based on the dry weight percentage of chitosan.

[0012] The beneficial effects of this invention are as follows:

[0013] 1. This invention is the first to discover that, compared to mature apples, young apples, which are agricultural waste during apple thinning, are rich in apple pectin, and are typically high-methyl ester pectin (methyl esterification degree greater than 50%), in which more than 50% of the galacturonic acid (GalA) carboxyl groups are methylated, thereby reducing the negative charge density on the fiber surface. Alkaline demethylation can effectively remove -COO groups from the apple pomace fibers. - Content from 0.15 mmol g -1 Increased to 1.30 mmol g -1 The mixture is homogenized under high pressure to form a gel-like solution of young apple nanofibers (YANF) with high aspect ratio and good water dispersibility. This YANF gel-like solution acts as a crosslinking agent, in which -COO - With the -NH3 in chitosan + Electrostatic cross-linking occurs, which significantly improves the hydrophobicity, mechanical strength and barrier properties of chitosan films.

[0014] 2. This invention determines that when using young apple fruit to prepare nanofiber crosslinking agents, alkaline demethyl ester treatment with 1M sodium hydroxide solution for 15 hours is the preferred process.

[0015] 3. This invention utilizes young apples, a byproduct of apple cultivation, to achieve the reuse of agricultural waste. Compared to the 20-day fermentation process required to produce BNC nanofiber crosslinking agent, YANF nanofiber crosslinking agent can be produced in one day, making it easier to obtain and scale up. This invention prepares a negatively charged YANF nanofiber crosslinking agent using young apples as raw material, with a carboxyl content of 3.80 ± 0.26 mM g. -1 With a zeta potential of -51.70±0.95mV and exhibiting excellent water dispersibility, it significantly improved the performance of chitosan films as an electrostatic crosslinking agent. Electrostatic crosslinking agents are increasingly used to improve the performance of polysaccharide-based films. Chitosan films containing 10% YANF nanofiber crosslinking agent (C-YANF-10) showed a significant increase in elongation at break from 17.36±0.71% to 20.32±0.30%, and tensile strength from 13.53±0.57MPa to 54.04±0.42MPa, exceeding the performance of existing composite films. Besides mechanical properties, barrier properties such as water vapor permeability (WVP), oxygen permeability (P'O2), and UV resistance are also important for expanding the applications of films. The WVP of C-YANF-10 increased from 0.895±0.055 ng / m³. -1 s -1 Pa -1 Decreased to 0.189±0.009ng m -1 s -1 Pa -1This effectively alleviated the fruit mold problem associated with high humidity. P'O2 also decreased from 829.94±23.55 mLμm. -2 day -1 atm -1 The concentration was significantly reduced to 356.55 ± 21.23 mL μm. -2 day -1 atm -1 The performance is comparable to that of polylactic acid (PLA) films. Compared to polyethylene (PE) and chitosan (CF) films, C-YANF-10 exhibits moderate WVP and lower P'O2, resulting in a reduction in the spoilage index of cherries from 100% (PE) and 35.83±1.44% (CF) to 4.17±1.44%, and a reduction in weight loss rate from 46.26±1.94% (CF) to 35.50±2.22%. Furthermore, the addition of 10% YANF enhances the UV-A blocking rate of the composite film to 99.56±0.16%, effectively preventing UV oxidation of food. Moreover, C-YANF-10 maintains excellent biodegradability, completely degrading within 15 days. Therefore, adding YANF nanofiber crosslinking agents during chitosan film preparation can improve the mechanical properties, barrier properties, and preservation properties of CF while maintaining its biodegradability. This film offers excellent preservation and environmental sustainability, providing tremendous potential for the future of sustainable food packaging. Attached Figure Description

[0016] Figure 1 Surface zeta potential diagram of apple young fruit fibers at different alkaline demethylation times;

[0017] Figure 2 The changes in zeta potential and degree of esterification on the surface of nanofibers in young apples with alkaline demethylation time;

[0018] Figure 3 X-ray diffraction patterns of young apple fruit fibers at different alkaline demethylation times;

[0019] Figure 4 Atomic force microscopy images of nanofibers from young apple fruits at different alkaline demethylation times;

[0020] Figure 5 Digital photographs of chitosan (CF), chitosan films containing 10% apple immature fruit nanofibers (C-YANF-10), and chitosan films containing 10% bacterial nanocellulose (C-BNC-10);

[0021] Figure 6 Surface zeta potential diagrams of apple young fruit nanofibers, chitosan, bacterial nanocellulose and their composite solutions;

[0022] Figure 7 The transmittance of chitosan and its films containing different amounts of apple immature fruit nanofibers and films containing different amounts of bacterial nanocellulose in the 300-800 nm spectral range;

[0023] Figure 8 The water vapor permeability of chitosan and its films containing different amounts of apple immature fruit nanofibers and films containing different amounts of bacterial nanocellulose;

[0024] Figure 9 The oxygen permeability coefficients of chitosan and its films containing different amounts of apple immature fruit nanofibers and films containing different amounts of bacterial nanocellulose;

[0025] Figure 10 The tensile strength and elongation at break of chitosan and films containing different amounts of apple immature fruit nanofibers and films containing different amounts of bacterial nanocellulose were studied.

[0026] Figure 11 The image shows the storage status of cherries within 10 days after they were not covered with plastic wrap, but covered with polyethylene, chitosan and films containing 10% apple immature fruit nanofibers or 10% bacterial nanocellulose.

[0027] Figure 12 The spoilage index of cherries stored for 10 days without plastic wrap, covered with polyethylene, chitosan and films containing 10% apple young fruit nanofibers or 10% bacterial nanocellulose.

[0028] Figure 13 The graph shows the rate of weight loss of cherries during a 10-day storage period, without plastic wrap, covered with polyethylene, chitosan, or films containing 10% apple immature fruit nanofibers or 10% bacterial nanocellulose.

[0029] Figure 14 The degradation of polyethylene, chitosan and their composite membranes containing 10% apple immature fruit nanofibers or 10% bacterial nanocellulose in soil over 15 days;

[0030] Figure 15 The weight loss rate of polyethylene, chitosan, and their films containing 10% apple immature fruit nanofibers or 10% bacterial nanocellulose in soil over 15 days. Detailed Implementation

[0031] The present invention will be further described below with reference to the embodiments.

[0032] Experimental materials:

[0033] The young apples were supplied by GreenTech Food Co., Ltd. (Hebei, China), referring to small apples harvested 2-3 weeks after pollination and before the physiological fruit drop period. Chitosan (degree of deacetylation: 90%, molecular weight: approximately 91 kDa) was purchased from Bluetech Technology Development Co., Ltd. (Shanghai, China). Spectroscopic grade potassium bromide was purchased from Aladdin (Shanghai, China). Unless otherwise specified, all reagents mentioned were analytical grade, purchased from Aladdin (Shanghai, China) Co., Ltd., and distilled water was used throughout the process.

[0034] Example 1: Preparation of crosslinking agent for young apple nanofibers:

[0035] Ten grams of dried young apple fruit were pulverized and added to a 1M sodium hydroxide solution at a weight ratio of 1:20. The mixture was then soaked at 25°C for 0, 5, 10, 15, and 20 hours for alkaline demethylation. The resulting fruit pomace was washed until neutral and named YAF-0h, YAF-5h, YAF-10h, YAF-15h, and YAF-20h, respectively. The samples were continuously processed using a high-pressure homogenizer (JN-Mini Pro, Guangzhou Juneng Nanobiotechnology Co., Ltd., China) at a pressure of 80 MPa. Water was added during the processing to obtain a 1% (w / w) gelatinous liquid rich in nanofibers with a diameter less than 25 nm, which was the crosslinking agent.

[0036] The morphology of nanofibers was measured using atomic force microscopy in tapping mode, and their length and diameter were analyzed using ImageJ 1.50i software. Zeta potentials were measured using a zeta potential analyzer. Carboxyl groups (-COO) were also analyzed. - The content was determined by conductivity titration according to the method of Saito and Isogai (2004). Chemical composition analysis, including neutral detergent fiber (NDF) and acid detergent fiber (ADF), was performed according to the method of Van Soest (1973). Pectin content was assessed using the carbazole-sulfuric acid colorimetric method described by Rodsamran et al. X-ray diffraction (XRD) patterns were obtained using a Bruker D8 Advance diffractometer to analyze crystallinity.

[0037] Chemical composition analysis revealed the main components of young apples. As shown in Table 1, the insoluble pectin in young apples (12.65 ± 0.12 wt%) was significantly higher than that in mature apples (approximately 8.0 wt%) by 4.65%. The insoluble pectin, rich in galacturonic acid units, provided a large amount of -COO₂. - This makes young apple fruit a promising raw material for nanofiber production. However, the high degree of methylation of galacturonic acid in young apple fruit fibers (70% esterification) results in low surface negative charge and weak electrostatic repulsion between fibers. Therefore, alkaline demethylation is a method to increase the -COO content on young apple fruit nanofibers.- A feasible method for determining the content. During alkaline treatment, both pH value and treatment time affect the effectiveness of alkaline demethylation. This example compares the effects of alkaline demethylation on dried young apples, which were pulverized and added to a 1M sodium hydroxide solution at a weight ratio of 1:20, and soaked at 25°C for 0, 5, 10, 15, and 20 hours, respectively. The results are shown in Table 1 and... Figure 1 :

[0038] Table 1. Yield, pectin, and carboxyl content of mature apple fiber and alkali-modified young apple fiber.

[0039]

[0040]

[0041] Note: Different lowercase letters in the same column indicate significant differences (P<0.05).

[0042] As shown in Table 1, as the alkali treatment time increased from 0 hours to 20 hours, the yield of YAF decreased from 67.38±3.49 wt% to 32.93±2.50 wt%, and the insoluble pectin content decreased from 12.65±0.12 wt% to 2.35±0.12 wt% (Table 1).

[0043] like Figure 1 As shown, with the alkali treatment time increasing from 0 hours to 15 hours, the negative zeta potential increased from -22.00±0.79mV to -51.70±0.95mV, reflecting an increase in electrostatic repulsion between the fibers of young apple fruits. Importantly, from Figure 2 It is evident that the negative zeta potential of all samples treated with alkaline demethylation exceeded -30 mV, indicating stable dispersion in water. Furthermore, as the alkaline treatment time increased from 0 hours to 15 hours, the degree of methylation decreased from 70.24 ± 1.00% to 9.23 ± 0.94%, and the -COO... - The content ranged from 0.06 ± 0.02 mM g. -1 Significantly increased to 3.80±0.26 mM g -1 (p<0.05)(Table 1). These results indicate that alkaline demethyl ester treatment effectively increased the negative charge density on the surface of young apple fruit fibers, thereby enhancing electrostatic repulsion and promoting the transformation of young apple fruit fibers into young apple fruit nanofibers.

[0044] To further investigate the effects of alkali treatment on the fibers of young apple fruits, X-ray diffraction (XRD) was used to analyze their crystal structure, such as... Figure 3As shown. Untreated YAF (YAF-0h) did not show any obvious crystallization peaks, while the alkali-treated samples (YAF-5h to YAF-20h) showed two distinct peaks at approximately 17° and 22°, corresponding to the (110) and (002) crystal planes, respectively. This change can be attributed to the removal of pectin, lignin, hemicellulose, and other compounds that previously masked the XRD signal of natural apple juvenile fibers. After alkali demethylation treatment, these masking substances were partially eliminated, thus exposing cellulose. Importantly, alkali demethylation treatment did not alter the crystalline structure of cellulose in apple juvenile fibers, which were still classified as type I cellulose. The crystallinity of apple juvenile fibers initially increased to 26.27% at 15 hours of treatment (YAF-15h) and then decreased at 20 hours, attributed to the gradual degradation of the cellulose crystalline structure. Generally, higher crystallinity enhances the mechanical and barrier properties of the film.

[0045] Atomic force microscopy images of nanofibers in young apples treated with different alkali times are shown below. Figure 4 As the treatment time increased from 0 h to 15 h, the fiber diameter significantly decreased from 28.03 ± 4.15 nm to 10.15 ± 2.10 nm, and the entanglement of the nanofiber network structure in young apple fruit weakened. This reduction is attributed to the hydrolysis of the methyl ester group on galacturonic acid in pectin, forming -COO groups. - The alkaline treatment increased electrostatic repulsion and weakened intermolecular / intramolecular hydrogen bonds, thus increasing the degree of fibrosis and reducing the entanglement of YANF. However, extending the alkaline treatment to 20 hours resulted in a slight increase in fiber diameter. This increase is due to the reduction of insoluble pectin caused by the β-elimination reaction, which lowers the surface charge of the apple immature fruit nanofibers and reduces the degree of fibrosis.

[0046] In summary, when using 1M sodium hydroxide solution for alkaline demethyl ester treatment, a treatment time of 15 hours is considered suitable for preparing crosslinking agents for young apple nanofibers.

[0047] Example 2: Preparation of chitosan film:

[0048] Chitosan films were prepared by casting. 2 g of chitosan was dissolved in 100 mL of 1% (v / v) acetic acid solution and stirred at room temperature for 4 hours. After complete dissolution, glycerol (30% of the chitosan mass) was added as a plasticizer and stirred for 0.5 hours. Then, apple young fruit nanofiber crosslinking agent obtained in Example 1 at different mass ratios (based on chitosan dry weight) was added, and the mixture was allowed to stand for 24 hours to remove air bubbles. 25 mL of the mixture was poured into a 9 cm diameter petri dish and dried in an oven at 45 °C for 12 hours to obtain chitosan films. Pure chitosan films were labeled CF, and composite films with 1%, 5%, and 10% chitosan mass percentages of apple young fruit nanofiber crosslinking agent were labeled C-YANF-1, C-YANF-5, and C-YANF-10, respectively. Since bacterial nanocellulose (BNC) is commonly used as a crosslinking agent to improve the performance of chitosan membranes, bacterial nanocellulose (BNC) was added at 1%, 5%, and 10% based on the mass percentage of chitosan as controls. The BNC composite films were labeled as C-BNC-1, C-BNC-5, and C-BNC-10, respectively.

[0049] All the films obtained above were stored in a desiccator and saturated Mg(NO3)2 solution with a relative humidity of 53% were added. After equilibration for 48 hours, they were used for further experiments.

[0050] 2.1. Comparison of the characterization of chitosan films in each group:

[0051] The thickness of the film was measured at multiple points, including the center, top, bottom, left, and right sides, using a Mitutoyo absolute digital micrometer. The volume of the film was derived from its thickness and area, while the density was calculated based on its mass-to-volume ratio. Transparency was measured using a 752 spectrophotometer (Beijing Haifuda Technology Co., Ltd., China), and the color of the composite film was determined using an NS808 colorimeter (Guangzhou Sanenshi Technology Co., Ltd., China). The experimental results are shown in Tables 2 and 3.

[0052] Table 2 Physical properties of chitosan films in each group

[0053]

[0054]

[0055] Note: Different lowercase letters in the same column indicate significant differences (P<0.05).

[0056] As shown in Table 2, the density of CF is 1.274 ± 0.005 g cm⁻³. After adding 1% YANF or BNC, the density of the composite film increases to approximately 1.300 g cm⁻³. -3There was no significant difference between the YANF and BNC composite films. However, when the addition amount increased to 10%, the density of C-YANF-10 increased to 1.378 ± 0.007 g / cm³. -3 It has a significantly higher density than C-BNC-10 (1.325 ± 0.004 g / cm³). -3 ).

[0057] Table 3. Color of chitosan films in each group

[0058]

[0059] Note: Different lowercase letters in the same column indicate significant differences (P<0.05).

[0060] Color and transparency are important factors affecting the appearance of the film. In this study, the Lab color model was used to evaluate the color of the composite film, where L* represents brightness, a* refers to the range from red to green, b* refers to the range from yellow to blue, and ΔE refers to the overall color difference. As shown in Table 3, the addition of BNC had no significant effect on L* (p<0.05), while the addition of YANF caused L* to gradually decrease with increasing YANF content. Compared with the CF film, the addition of BNC and YANF significantly increased the a*, b*, ΔE values ​​and opacity of the composite film (p<0.05), resulting in a distinct pale yellow color. The addition of both YANF and BNC significantly increased the opacity; at the same concentration, the opacity of the YANF composite film was significantly higher than that of the BNC composite film (p<0.05). The increased opacity is due to the increased light scattering and reduced transmittance caused by the electrostatic crosslinking between YANF and chitosan. Notably, the YANF composite film exhibited a brownish-yellow appearance because YANF contains polyphenols and lignin, which deepen the color. This color can reduce photochemical oxidation of food caused by ultraviolet and visible light, potentially reducing nutrient loss.

[0061] like Figure 5 As shown, all samples with a thickness of 0.1 mm exhibited transparency, making the underlying background pattern clearly visible. This observation indicates that the addition of BNC and YANF does not affect the film's transparency. To further evaluate the effect of YANF on the physical properties of the chitosan film, the difference was attributed to the different interactions between BNC and YANF with chitosan. To reveal the interaction between YANF and chitosan, the zeta potentials of YANF, BNC, and their mixed solutions with chitosan were measured at pH = 2. Figure 6As shown, the zeta potential of the BNC solution is 5.13 ± 0.46 mV, while that of the chitosan solution is 65.47 ± 0.61 mV, decreasing to 52.53 ± 1.56 mV after mixing with BNC. Conversely, the zeta potential of the YANF solution is -20.70 ± 2.21 mV, significantly decreasing to 9.29 ± 1.15 mV after mixing with chitosan. This indicates that BNC mainly interacts with chitosan through non-electrostatic interactions such as hydrogen bonding, while YANF interacts with chitosan through electrostatic crosslinking, thereby forming a denser structure within the chitosan film.

[0062] 2.2 Comparison of the solubility and swelling degree of chitosan films in each group:

[0063] To evaluate the water-blocking properties of the chitosan composite film, we cut the composite film into 2cm × 2cm pieces for solubility and swelling. As shown in Table 4, the solubility of CF was 28.27 ± 0.25%, indicating relatively poor water-blocking ability, which limits its application in food preservation and other fields. The solubility decreased after the addition of BNC and YANF. Specifically, when the concentrations of BNC and YANF increased from 1% to 10%, the solubility of the YANF composite film decreased from 24.68 ± 0.59% to 18.54 ± 0.34%, significantly lower than that of C-BNC-10 (23.39 ± 0.26%) (p < 0.05). Similarly, the swelling rate of CF was 598.17 ± 28.49%, and the addition of YANF and BNC significantly reduced the swelling rate. As the YANF concentration increased from 1% to 10%, the expansion rate of the YANF composite film decreased from 79.19±0.63% to 27.22±1.14%, significantly lower than that of C-BNC-10 (32.86±0.34%) (p<0.05). This improvement is attributed to the -COO content of YANF. - and chitosan's -NH3 + The electrostatic crosslinking between the two components forms a denser crosslinked network structure. This reduces the exposure of hydrophilic hydroxyl groups and lowers the sensitivity to water, which is more effective than the hydrogen bond crosslinking between BNC and chitosan. Therefore, the water-blocking performance of the YANF composite film is better than that of the BNC composite film, indicating that YANF can more effectively enhance the water-blocking performance of chitosan films.

[0064] Table 4. Hydrophilic properties of the composite film

[0065]

[0066] Note: Different lowercase letters in the same column indicate significant differences (P<0.05).

[0067] 2.3 Comparison of the UV blocking performance of each group of chitosan films:

[0068] The UV blocking performance of the composite film was evaluated using UV-Vis spectroscopy. Figure 7 The UV-A and UV-B blocking properties of CF were 84.63±0.66% and 97.27±0.16%, respectively. As the YANF content increased from 1% to 10%, the UV-A blocking property improved from 89.92±0.61% to 99.56±0.16%, and the UV-B blocking property reached 99.98±0.01%, significantly exceeding the values ​​of the C-BNC-10 film (UV-A blocking: 95.14±0.56%, UV-B blocking: 99.40±0.06%). These results indicate that YANF significantly improves the UV blocking performance of chitosan films, making them ideal for food packaging applications that prevent UV-induced oxidation and degradation of fruits.

[0069] 2.4 Comparison of the gas barrier properties of each group of chitosan films:

[0070] Water vapor permeability (WVP) was determined according to the method of Lucía Famá et al. The oxygen permeability coefficient (P'O2) of the film was evaluated using a C26H permeability tester. Water vapor permeability (WVP) is a key parameter in food packaging; blocking water vapor helps extend the shelf life of food and maintain its freshness and flavor. Figure 8 As shown, the WVP of CF is 0.895 ± 0.055 ng m - 1 s -1 Pa -1 The WVP of the composite film was significantly reduced upon the addition of YANF and BNC (p<0.05). Specifically, the WVP decreased to 0.189±0.009 ng / m³ after the addition of 10% YANF. -1 s -1 Pa -1 It was significantly lower than the 0.389±0.006 ng m of C-BNC-10. -1 s -1 Pa -1 (p<0.05). However, the WVP values ​​of traditional petroleum-based materials such as polyethylene (PE) are significantly lower, approximately 2.300*10. -7 ng m -1 s - 1 Pa -1 In fruit preservation, the endogenous water produced by plant respiration increases the moisture content during storage and promotes microbial growth. Therefore, the moderate WVP of C-YANF-10 can provide a suitable balance for effective preservation.

[0071] Oxygen can damage the color, flavor, and nutritional components of food, negatively impacting its preservation. Food preservation films mitigate this problem by reducing oxygen permeability, thereby slowing the respiration rate of fruit. To evaluate the effectiveness of these films, we measured their oxygen permeability coefficient (P'O2). Figure 9 The P'O2 value of the composite film is shown. The P'O2 value of CF is 829.94 ± 23.55 mL μm. -2 day -1 atm -1 As the YANF concentration increased from 1% to 10%, the P'O2 value of the YANF composite membrane increased from 526.80 ± 21.09 mL / μm. -2 day -1 atm -1 It decreased significantly to 356.55 ± 21.55 mL μm. -2 day -1 atm -1 The P'O2 value was significantly lower than that of the C-BNC-10 composite membrane (643.23 ± 26.85 mL μm). -2 day -1 atm -1 These results demonstrate that YANF significantly improves the oxygen barrier properties of chitosan films. YANF forms a dual-network structure with chitosan through electrostatic crosslinking and hydrogen bonding, prolonging the diffusion path of oxygen in the composite film and thus improving its oxygen barrier performance. Specifically, under 0% relative humidity conditions, the P'O2 of C-YANF-10 is significantly lower than that of polyethylene (PE, 50,000-200,000 mL / μm). -2 day -1 atm -1 ) and polypropylene (PP, 50,000-100,000 mL μm m -2 day -1 atm -1 Commercial petroleum-based films are about 2-3 orders of magnitude lower in viscosity than polylactic acid (PLA), which has a viscosity of ~300 mL / μm. -2 day -1 atm -1 The C-YANF-10 composite film has a moderate WVP and lower P'O2 compared to polyethylene. This balance helps maintain a low-water, low-oxygen environment, reducing spoilage caused by microbial growth due to respiration and high humidity, thereby improving fruit preservation.

[0072] 2.5 Comparison of the mechanical properties of each group of chitosan films:

[0073] Mechanical properties were measured using a 34TM-5 universal material testing machine, and tensile strength and elongation at break were calculated.

[0074] Mechanical properties are important indicators for measuring the toughness and tear resistance of food packaging. For example... Figure 10 As shown, the elongation at break and tensile strength of CF were 17.36±0.71% and 13.53±0.57 MPa, respectively. These unsatisfactory mechanical properties limit its application in food packaging. However, the addition of different amounts of BNC and YANF significantly affected the mechanical properties of the film (p<0.05). Increasing the YANF content from 1% to 10% increased the tensile strength of the composite film by 153.59%, from 21.31±0.52 MPa to 54.04±0.42 MPa, comparable to the tensile strength of the BNC composite film (55.77±1.25 MPa). This indicates that YANF significantly improved the tensile strength. With increasing YANF content, the elongation at break of the composite film initially increased from 25.87±0.35% (C-YANF-1) to 32.10±0.85% (C-YANF-5), then decreased to 20.32±0.30% (C-YANF-10) at higher YANF contents. In contrast, within the same range, the elongation at break of BNC decreased from 15.47±0.35% (C-BNC-1) to 11.30±0.05% (C-BNC-10), remaining lower than that of CF.

[0075] The elongation at break of the composite film is mainly affected by two factors: first, the -COO in YANF pectin. - When polysaccharides are in an amorphous state, hydrogen bonding with glycerol reduces crystallinity and increases molecular chain fluidity, thereby increasing the flexibility of chitosan films (CF). Conversely, bicarbonate (BNC) reduces the elongation at break of the composite film. Secondly, the electrostatic crosslinking between YANF and chitosan also affects the elongation at break. When the YANF concentration does not exceed 5%, the crosslinking density is moderate and can maintain the elongation at break. However, when the YANF concentration reaches 10%, excessively high crosslinking density reduces the elongation at break. Therefore, YANF can serve as an effective electrostatic crosslinking agent, significantly improving the mechanical properties of chitosan films.

[0076] Example 3: Verification of the preservation effect on cherries:

[0077] Cherries were placed in 300 ml disposable clear plastic cups, either unsealed (control group) or sealed with PE, CF, C-YANF-10, or C-BNC-10 preservative film. All samples were stored at room temperature for 10 days. Weight loss was recorded every 2 days. Cherries were graded, with particular emphasis on assessing surface rot. The grading system used five grades based on rot severity: Grade 0: intact skin, no browning or rot; Grade 1:

[0078] Grade 1: Slight browning or denting of the peel, with an affected area of ​​≤10%; Grade 2: Obvious browning of the peel, with a rotten area of ​​10% to 30%; Grade 3: Obvious browning bands, with a rotten area of ​​30% to 50%; Grade 4: Rotten area of ​​more than 50%.

[0079] Experimental results are as follows Figure 11 As shown, uncovered cherries (control group) began to mold on day 4 and showed signs of weight loss and shrinkage on day 6. In contrast, cherries covered with CF (C-YANF-10) showed better preservation, with mold and shrinkage delayed until day 5 and day 7, respectively. Cherries covered with C-YANF-10 did not show significant shrinkage throughout the storage period, and the occurrence of mold and shrinkage was also delayed until day 10, comparable to the performance of C-BNC-10. To demonstrate the preservative effect of C-YANF-10, commercial polyethylene (PE) was used as a positive control. After 10 days, although polyethylene successfully prevented cherry shrinkage, the cherries began to mold on day 5, indicating that its preservation effect was significantly inferior to C-YANF-10. These results confirm that YANF can significantly improve the preservation performance of chitosan films.

[0080] During storage, respiration in cherries activates hydrolytic enzymes, such as those that convert insoluble polysaccharides into soluble sugars (e.g., converting starch into glucose). This process accelerates overripeness, making the skin more susceptible to fungal invasion and decay, consuming nutrients such as glucose and fructose, and increasing weight loss. To further evaluate the preservation effect of the YANF composite film, we assessed the decay index and weight loss rate of cherries. Figure 12 The decay index of cherries under different treatments is shown. On days 0-2, the decay index of the PE group was 0.83 ± 1.44% higher than the other groups. After 4 days, the PE group had the highest decay index at 8.33 ± 1.44%, followed by the uncapped group at 3.33 ± 1.44%, while the CF group had the lowest decay and browning indices. Notably, the C-YANF-10 and C-BNC-10 groups showed no decay or browning. After 10 days, the decay index of the uncapped and PE groups increased significantly, with the PE group showing complete decay (100%) and the uncapped group at 64.17 ± 3.82%, higher than the CF group's 35.83 ± 1.44%. Conversely, the decay indices of the C-YANF-10 and C-BNC-10 groups were lower, at 4.17 ± 1.44% and 10.67 ± 1.15%, respectively. Figure 13The weight loss rate of cherries during 10 days of storage was shown. The polyethylene group had the lowest weight loss rate, while the uncovered group had a higher weight loss rate, which was attributed to increased moisture evaporation due to prolonged exposure to air. After 10 days, the weight loss rate of the uncovered group reached 66.39±1.59%, significantly higher than other sealing treatments. The weight loss rates of the C-YANF-10 and C-BNC-10 groups were 35.50±2.22% and 38.27±1.34%, respectively, significantly lower than the uncovered and CF groups. This result is attributed to the consumption of oxygen and production of carbon dioxide during cherry respiration. Although the polyethylene film has high gas barrier properties, resulting in a lower weight loss rate, it traps water vapor, creating a high-humidity environment conducive to microbial growth and accelerated decay. In contrast, C-YANF-10 has moderate water vapor permeability, effectively delaying respiration and reducing decay, demonstrating a significant preservative effect.

[0081] Example 4, Biodegradation Test:

[0082] Biodegradable plastics refer to plastics that degrade under natural conditions through microorganisms (such as bacteria, molds, and algae), ultimately mineralizing into CO2, H2O, inorganic salts, and new biomass. However, traditional petroleum-based films are difficult to degrade, leading to environmental problems such as "white pollution." To evaluate the biodegradability of YANF composite films, biodegradation experiments were conducted in Xi'an, China (34°12'22.55"N, 108°57'11.71"E). The test films were PE, CF, C-YANF-10, or C-BNC-10 films, sealed, weighed, and buried 5 cm below the soil surface. Water was sprayed every two days to ensure consistent humidity. Samples were weighed every 5 days to calculate the biodegradation rate.

[0083] The appearance of these films during the degradation process is as follows Figure 14 As shown, CF and its composite films both exhibited biodegradability, while PE did not degrade. Specifically, the CF film completely degraded on day 15. C-YANF-10 showed slight fracturing on day 5 and completely degraded on day 15. Conversely, C-BNC-10 began to crack on day 10 and fractured on day 15, but did not completely degrade. Further characteristics of biodegradability are shown in [link to documentation]. Figure 15 Both CF and C-YANF-10 showed a 100% weight loss rate within 15 days, while C-BNC-10 showed a weight loss rate of 59.49 ± 2.68%. CF's degradation rate was 9.31 g / day in the first 10 days. In contrast, C-YANF-10 degraded more slowly in the first 5 days at 1.13 g / day, but the degradation rate accelerated to 11.90 g / day between days 5 and 10. This change is attributed to the -COO- in YANF and the -NH3 in chitosan. +Electrostatic cross-linking between the molecules forms a dual-network structure. This structure reduces surface hydrophilicity, increases microbial resistance, and initially slows the degradation rate of C-YANF-10. However, once the dual-network structure is disrupted, the degradation rate accelerates significantly. This highlights the potential of C-YANF-10 for sustainable packaging applications.

[0084] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0085] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A crosslinking agent for improving the performance of chitosan films, characterized in that, The crosslinking agent is a gel-like liquid rich in nanofibers with a diameter of less than 25 nanometers and a mass fraction of 0.5%-1.5%. The nanofibers are extracted from young apple fruits, which are small apples removed within 2-3 weeks after pollination and before the physiological fruit drop period.

2. The method for preparing the crosslinking agent for improving the performance of chitosan films according to claim 1, characterized in that, The crosslinking agent is prepared by pulverizing dried young apples and adding them to a 0.1-4 M sodium hydroxide solution at a weight ratio of 1:10-50. The mixture is then soaked at room temperature for 10-30 hours for alkaline demethylation. The resulting fruit pomace is then washed with water until neutral. The neutral fruit pomace is then processed several times using a high-pressure homogenizer, with water added during the processing. This process yields a colloidal liquid rich in nanofibers with a diameter of less than 25 nanometers and a mass fraction of 0.5%-1.5%, which is the crosslinking agent.

3. The method for preparing the crosslinking agent according to claim 2, characterized in that, The crushed young apples were added to a sodium hydroxide solution at a ratio of 1:

20.

4. The method for preparing the crosslinking agent according to claim 3, characterized in that, The sodium hydroxide solution was 1M, and the solution was soaked for 15 hours to perform alkaline demethylation.

5. The application of the crosslinking agent according to any one of claims 1-4 in the preparation of chitosan films, characterized in that, Chitosan is dissolved in acetic acid solution and stirred until completely dissolved. Then, a plasticizer is added and stirred until completely dissolved. Next, the crosslinking agent is added at a concentration of 1%-15% based on the dry weight percentage of chitosan. After mixing evenly, the mixture is allowed to stand until all air bubbles are removed. The mixture is then poured into a mold, leveled, and dried at low temperature to obtain the chitosan film.

6. The application of the crosslinking agent according to claim 5 in the preparation of chitosan films, characterized in that, The crosslinking agent is added at a concentration of 10% based on the dry weight percentage of chitosan.